Formation of Self-Organized Mn3O4 Nanoinclusions in LaMnO3 Films - Pomar, Alberto; Konstantinović, Zorica; Bagués, Núria; Roqueta, Jaume; López-Mir, Laura; Balcells, Lluis; Frontera, Carlos; Mestres, Narcis; Gutiérrez-Llorente, Araceli; Šćepanović, Maja; Lazarević, Nenad; Popović, Zoran V.; et al. (Frontiers in Physics, 2016)
We present a single-step route to generate ordered nanocomposite thin films of secondary phase inclusions (Mn3O4) in a pristine perovskite matrix (LaMnO3) by taking advantage of the complex phase diagram of manganese oxides. We observed that in samples grown under vacuum growth conditions from a single LaMnO3 stoichiometric target by Pulsed Laser Deposition, the most favourable mechanism to accommodate Mn2+ cations is the spontaneous segregation of self-assembled wedge-like Mn3O4 ferrimagnetic inclusions inside a LaMnO3 matrix that still preserves its orthorhombic structure and its antiferromagnetic bulk-like behaviour. A detailed analysis on the formation of the self-assembled nanocomposite films evidences that Mn3O4 inclusions exhibit an epitaxial relationship with the surrounding matrix that it may be explained in terms of a distorted cubic spinel with slight ( 9º) c-axis tilting. Furthermore, a Ruddlesden-Popper La2MnO4 phase, helping to the stoichiometry balance, has been identified close to the interface with the substrate. We show that ferrimagnetic Mn3O4 columns influence the magnetic and transport properties of the nanocomposite by increasing its coercive field and by creating local areas with enhanced conductivity in the vicinity of the inclusions.